Hyzic, the Hydra homolog of the zic/odd-paired gene, is involved in the early specification of the sensory nematocytes - Lindgens, Dirk; Holstein, Thomas W. (Development, 2004)
Cnidaria are the first class of organisms in animal evolution with a nervous system. The cnidarian Hydra has two types of neuronal cell, nerve cells and nematocytes. Both differentiate from the same pool of pluripotent stem cells. Yet, the molecular regulation of neural differentiation in Hydra is largely unknown. Here, we report the identification of Hyzic, a homolog of the Zn-finger transcription factor gene zic/odd-paired, which acts as an early neural effector gene in vertebrates. We show, that Hyzic is expressed in the early nematocyte differentiation pathway, starting at the level of interstitial stem cells. Expression of Hyzic is restricted to the proliferative stages of nematoblasts. Hyzic acts before and possibly directly upstream of Cnash, a homolog of the proneural bHLH transcription factor gene achaete-scute, and of Nowa, an early nematocyte differentiation marker gene. Hyzic may determine stem cells to differentiate into nematocytes. Our data are consistent with a role of Hyzic in inhibiting nematocyte differentiation, by keeping committed nematoblast cells in the cell cycle. A similar role has been demonstrated for Zic genes in vertebrates. Our results suggest, that genetic cascades of neural development may be conserved from Hydra to vertebrates, indicating that the molecular regulation of neural development evolved only once.